Estimation of Adult Human Height from the Bigonial Width and Mandibular Arch - Aragão, José Aderval; Santana, Guilherme Machado de; Sacramento, Erick Mendonça do; Marcelo, Israel Santos; Aragão, Iapunira Catarina Sant'Anna; Sant'Anna Aragão, Felipe Matheus; Reis, Francisco Prado (Journal of Morphological Sciences, 2019)
Introduction An individual's sex, age and height are of great importance in legal medicine, especially with regard to identifying corpses. Height estimates are based on the proportionality relationship that exists between an individual's height and his various body parts.Objective To analyze the relationship between mandible measurements (length of the mandibular arch and bigonial width) and height.Materials and methods This study was conducted on the population of the Mussuca quilombo settlement, which is in the municipality of Laranjeiras, state of Sergipe, Brazil. The sample was composed of 300 individuals: 150 women and 150 men aged between 18 and 85 years old. The statistical analysis was done using the Statistical Package for the Social Scienes SPSS®, version 19.0, for Windows (SPSS Inc., Chicago, EUA) and Excel 2010 (Microsoft Corp., Redmond, WA, USA).Results The correlation coefficients were found to be low, with weak correlations between the measurements of the mandibula and height. Analysis on these values shows a very small positive correlation between height and the length of the mandibular arch among males (r = 0.177; p < 0.05) and among females (r = 0.271; p = 0.001); and between height and bigonial width among females (r = 0.169; p < 0,05).Conclusion Height may be estimated less exactly in cases in which only cephalofacial dimensions are available for legal medical examination.
Keywords: anatomy and anthropology; anthropometry; body height; forensic anthropology; jaw; legal medicine